Implications of nest relocation for morphology and locomotor performance of green turtle (Chelonia mydas) hatchlings. (15th June 2021) - Tanabe, Lyndsey K.; Steenacker, Marion; Rusli, Mohd Uzair; Berumen, Michael L.
Abstract: Sea turtle scute abnormalities are observed in higher proportion in hatchlings compared to adults, suggesting that hatchlings with a non-modal scute pattern (NMSP) have a lower chance of surviving to adulthood. In this study, we collected 732 newly emerged hatchlings from Redang Island, Malaysia, and compared their scute classification, size, and mass to fitness correlates (self-righting ability, crawling speed, and swimming speed). We investigated the proportion of hatchlings from each nest with NMSP to determine if there was a correlation with incubation duration or clutch relocation. We found relocated clutches at Chagar Hutang Turtle Sanctuary had a significantly shorter incubation duration with a higher proportion of NMSP compared to in situ clutches. Hatchlings' mass were significantly heavier from in situ clutches compared to relocated clutches, although there were no significant differences of hatchling speed based on scute classification or clutch type. The difference of hatchling mass between in situ and relocated clutches could affect predation and mortality rates on recently emerged hatchlings. These findings have important conservation implications, suggesting that relocation should only be implemented on clutches with a high potential to be disrupted or with a low chance of survival if left in situ . Our findings highlight the need for a standard procedure when clutch relocation is used as a conservation strategy. Relocation should replicate natural nest dimensions by duplicating both nest width and depth, and clutches should be relocated to similar shade conditions as the natural nest. Graphical abstract: Image 1 Highlights: We assessed the effects of clutch relocation (a conservation technique) on hatchling quality. Relocated clutches had a shorter incubation duration compared to in situ clutches. Hatchlings from relocated clutches had more non-modal scute patterns, which might affect their survival to adulthood. Hatchlings from in situ clutches were significantly heavier than hatchlings from relocated clutches. Relocation may not be an ideal management approach; if used, nest shape and depth should duplicate the in situ nest.